BK Polyomavirus‐Specific Cellular Immune Responses Are Age‐Dependent and Strongly Correlate With Phases of Virus Replication. Issue 6 (11th April 2014) - Schmidt, T.; Adam, C.; Hirsch, H. H.; Janssen, M. W. W.; Wolf, M.; Dirks, J.; Kardas, P.; Ahlenstiel‐Grunow, T.; Pape, L.; Rohrer, T.; Fliser, D.; Sester, M.; et al.
<x xml:space="preserve">Abstract</x> BK polyomavirus (BKPyV) infection is widespread and typically asymptomatic during childhood, but may cause nephropathy in kidney transplant recipients. However, there is only limited knowledge on BKPyV‐specific immunity in children and adults, and its role in BKPyV‐replication and disease posttransplant. We therefore characterized BKPyV‐specific immunity from 122 immunocompetent individuals (1–84 years), 38 adult kidney recipients with (n = 14) and without BKPyV‐associated complications (n = 24), and 25 hemodialysis (HD) patients. Blood samples were stimulated with overlapping peptides of BKPyV large‐T antigen and VP1 followed by flow‐cytometric analysis of activated CD4 T cells expressing interferon‐γ, IL‐2 and tumor necrosis factor‐α. Antibody‐levels were determined using enzyme‐linked immunosorbent assay. Both BKPyV‐IgG levels and BKPyV‐specific CD4 T cell frequencies were age‐dependent (p = 0.0059) with maximum levels between 20 and 30 years (0.042%, interquartile range 0.05%). Transplant recipients showed a significantly higher BKPyV‐specific T cell prevalence (57.9%) compared to age‐matched controls (21.7%) or HD patients (28%, p = 0.017). Clinically relevant BKPyV‐replication was associated with elevated frequencies of BKPyV‐specific T cells (p = 0.0002), but decreased percentage of cells expressing multiple cytokines (p = 0.009). In conclusion, BKPyV‐specific cellular immunity reflects phases of active BKPyV‐replication either after primary infection in childhood or during reactivation after transplantation. Combined analysis of BKPyV‐specific T cell functionality and viral loads may improve individual risk assessment.